Ratio of roughage to grain for fattening steer calves. - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This is a preliminary report covering the first 98 days of this feeding trial which is still being conducted; therefore the reader should bear in mind that the figures are in no way conclusive or complete. The physical balance or ratio of roughage to concentrates is an important factor to consider in the ration of fattening cattle. Beef cattle serve as one of the principal means of marketing roughage. Since a large amount of roughage is produced throughout the Midwest, it is desirable to have information concerning the maximum amount of roughage that can be used in fattening rations consistent with maximum and economical production. This experiment was planned to secure information on the effects of different levels of roughage on average daily gain, feed requirement per unit of gain, quality of finish, selling price, and carcass quality.
Keywords: Beef; Roughage; Steer; Gain; Carcass quality